2016
DOI: 10.1053/j.ajkd.2015.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Novel Once-Daily Extended-Release Tacrolimus Versus Twice-Daily Tacrolimus in De Novo Kidney Transplant Recipients: Two-Year Results of Phase 3, Double-Blind, Randomized Trial

Abstract: Results suggest that once-daily LCPT in de novo kidney transplantation has comparable efficacy and safety profile to that of IR-Tac. Lower TDD reflects LCPT's improved bioavailability and absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 38 publications
4
55
0
1
Order By: Relevance
“…Our data suggest that Fen has greater immunosuppressive effects than Dex. Fentanyl may therefore allow reduced doses of immunosuppressive drugs to decrease cardiac or nephrotoxic adverse effects of immunosuppressive drugs 23 in the induction period. A study to determine the additive/synergic effects of Fen and Dex with calcineurin inhibitors in HTx models in mice is currently in progress in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that Fen has greater immunosuppressive effects than Dex. Fentanyl may therefore allow reduced doses of immunosuppressive drugs to decrease cardiac or nephrotoxic adverse effects of immunosuppressive drugs 23 in the induction period. A study to determine the additive/synergic effects of Fen and Dex with calcineurin inhibitors in HTx models in mice is currently in progress in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…This extended‐release once‐daily tablet (LCPT) increases the bioavailability of tacrolimus by the creation of a solid dispersion, or a solid solution, of the drug substance through a physical process called “controlled agglomeration.” Prior randomized trials in renal transplant recipients comparing LCPT with IR‐Tac have shown that LCPT has greater bioavailability, a steadier and more consistent concentration time profile over 24 hours, and reduced fluctuation (the peak‐to‐trough change in drug concentrations around the average concentration) and swing (the peak‐to‐trough change in drug concentrations relative to the minimum concentration) compared to IR‐Tac . In addition, LCPT has demonstrated comparable efficacy, improved tolerability in regard to hand tremors, and robust correlations between area under the concentration‐time curve (AUC) and minimum whole blood concentration (C min ) in trials evaluating the product in renal transplantation …”
mentioning
confidence: 99%
“…Although the detailed mechanism regarding less class ll DSA and ABMR in TAC‐QD is unclear, our results suggested contribution of the different PK properties including diurnal variability. Rostaing et al reported 2‐year results regarding novel TAC‐LCPT using MeltDose drug delivery technology. TAC‐LCPT showed a lack of diurnal variability and lower TAC peak concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…TAC is available as an immediate‐release twice‐daily capsule (TAC‐BID) and extended‐release once‐daily capsule (TAC‐QD). Furthermore, once‐daily TAC is available as a capsule (Astagraf XL, Advagraf, and Prograf‐XL) and tablet (TAC‐LCPT; Envarsus XR) . TAC‐QD has the potential for improving treatment adherence compared with TAC‐BID .…”
Section: Introductionmentioning
confidence: 99%